Pengaruh Fleksibilitas Kognitif Guru dan Kinerja Guru Terhadap Prestasi Belajar Siswa pada Mata Pelajaran PAI di SMAN 1 Rejang Lebong - Mutia Yurika (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
Abstract. This research is about the influence of teacher cognitive flexibility and teacher performance on student learning achievement in islamic religious education subjects at high school 1 rejang lebong. This research has following objectives: (1). To find the influence of teacher cognitive flexibility on student learning achievement in islamic religious education subjects at high school 1 rejang lebong. (2). To find the and teacher performance on student learning achievement in islamic religious education subjects at high school 1 rejang lebong. (3). the influence of teacher cognitive flexibility and teacher performance on student learning achievement in islamic religious education subjects at high school 1 rejang lebong using quantitative research, data collection observation, questionnaires and documentation. Data wettability technique uses triangulation techniques. Data validation techniques use data reduction methods, presenting data and drawing conclusions. The results of this study are 1) Cognitive Flexibility (X1) has a significant effect on learning achievement (Y) with a calculated t value of 0.481 with a sig of 0.028. Sig analysis results. 0.028 is smaller than 0.05, meaning that individually the Cognitive Flexibility variable (X1) has a significant effect on learning achievement (Y). 2) Teacher performance (X2) has a significant effect on learning achievement (Y) with the calculated t value of Teacher Performance (X2) being 0.536 with a sig of 0.002. Sig analysis results. 0.041 is smaller than 0.05, meaning that individually the Teacher Performance variable (X2) has a significant effect on learning achievement (Y). 3) Cognitive Flexibility (X1) and Teacher Performance (X2) have a significant influence on learning achievement (Y) with a calculated F value of 2.316 with F sig. 0.003 where F sig. 0.003 is smaller than 0.05.